Zerumbone ameliorates neuroinflammation in LPS-induced SH-SY5Y cells, an in vitro model of neuropathic pain: targeting NO, IL-6, and TNF-α - Mohammed Izham, Noor Aishah; Perimal, Enoch Kumar; Vidyadaran, Sharmili; Bharatham, Hemabarathy (Neurotak Publishing, 2025)
Neuropathic pain is initiated by lesions or diseases affecting the somatosensory nervous system. The development and persistence of this condition involve complex and interconnected mechanisms, including those related to neuroinflammation and neuronal hyperexcitability. Due to an incomplete understanding of these mechanisms, conventional therapies for neuropathic pain often result in adverse effects. Recent research has proposed that zerumbone, a crystalline sesquiterpene compound extracted from Zingiber zerumbet, can attenuate neuropathic pain in animal models. Lipopolysaccharide (LPS)-induced SH-SY5Y cells were employed to allow tight control of the physiological environment, which could not be established in in vivo models, in addition to reducing the use of animals in the study of neuropathic pain. LPS induction in SH-SY5Y cells enables the observation of one of the hallmarks of neuropathic pain pathophysiology, which is the expression of pro-inflammatory mediators. This study aims to evaluate the anti-inflammatory effect of zerumbone by measuring its influence on the expression of nitric oxide (NO), interleukin-6 (IL-6), and tumour necrosis factor-alpha (TNF-α) in LPS-induced SH-SY5Y cells, an in vitro model of neuropathic pain. The anti-neuroinflammatory effect of zerumbone was first investigated through the expression level of NO, whereby the inhibitory concentration of zerumbone was determined at 8 μg/ml (p<0.0001 compared to the LPS-only group). Zerumbone treatment significantly reduced the expression of IL-6 (p<0.05 compared to the LPS-only group). Although a reduction in TNF-α levels was observed, it did not reach statistical significance in the enzyme-linked immunoassay (ELISA). Data from each experiment were analysed by using the One-way Analysis of Variance (ANOVA) followed by the post hoc Tukey test, p<0.05. Zerumbone demonstrates an anti-neuroinflammatory effect in LPS-stimulated SH-SY5Y cells by suppressing the expression of key inflammatory mediators NO, IL-6, and TNF-α. These findings suggest that zerumbone is a potential therapeutic candidate for managing neuropathic pain associated with neuroinflammation.